Bacterial Endocarditis Caused by Sphingomonas paucimobilis: A Case Report and Literature Review - Kara Rognrud; Andrew M. Diaz; Collin Hill; Melissa A. Kershaw (Case Reports in Infectious Diseases)
A 47-year-old male with no significant medical history was hospitalized for bacteremia and diagnosed with endocarditis. The organism isolated was a Gram-negative bacillus—Sphingomonas paucimobilis. There are only a few reported cases of endocarditis caused by S. paucimobilis, and to our knowledge, this is the first in the United States.